Efektivitas Pengajian Malam Jum’at Dalam Membangun Karakter (Studi Kasus: Majelis Taklim Masjid Nurhidayah Sidenreng Rappang) - Abdul Malik Tibe; Abdul Kadir; Alwardi Alwardi (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Education constitutes a pivotal dimension within human existence, and this endeavor can manifest in diverse modalities, including non-formal methodologies; one significant medium through which knowledge can be disseminated is through university studies. Besides serving as a form of non-formal education, this initiative is perceived to yield numerous advantages, among which character development is paramount; this investigation was conducted with the objective of assessing the efficacy of the regular Friday night study sessions held at the Hidayah Mosque in Padangloang Village, Sidenreng Rappang District. This research employs a qualitative framework, underpinned by a phenomenological approach that scrutinizes a phenomenon that remains entirely unaffected by human intervention. The findings of this investigation indicate that the consistent Friday night study sessions exert a substantial influence on the character development of the Taklim assembly participants at the Nurhidayah Mosque, as evidenced by their behavioral attitudes; in addition to fostering greater harmony with their neighbors, this study also cultivates an elevated sense of social cohesion and unity. Furthermore, this initiative has repercussions for enhancing the comprehension and profundity of knowledge among the worshippers, guiding them toward an improved existence grounded in Islamic principles, which serves as the cornerstone for cultivating virtuous morals.